Peran Humas Pondok Modern Darusslam Gontor (PMDG) dalam Membangun Lembaga Pendidikan - Abdullah Abdullah; Deden Mauli Darajat (Universitas Darussalam Gontor collaboration with ISKI (Ikatan Sarjana Ilmu Komunikasi Indo, 2016)
AbstractPublic relations plays an important role in an institution including for boarding school or so-called Pondok Pesantren. Pondok Pesantren is an Islamic education system used by some Moslem-majority countries. In Moslem-majority countries including in Indonesia, Islamic education has shown significant improvements. Therefore, Pondok Pesantren in Indonesia needs to implement best practices from other Islamic institutions in the world. One the most prominent Pondok Pesantren in Indonesia is Pondok Modern Darussalam Gontor (henceforth referred to as PMDG). In the beginning of its inception, founding fathers of PMDG visited some prominent educational institutions around the world especially the ones which are suitable with PMDG’s values. In Egypt, there is Al-Azhar University which is well-known for its eternal waqaf, being able to give scholarships to students around the world. In Libya there is Pondok Syanggit, famous for its Pondok managers’ generosity and sincerity. In India, there is Aligarh Muslim University famous as a pioneer in modern educational revival of Islam. The next is Shantiniketan in India which was founded by Rabindranath Tagore, a Hindu philosopher, located in the middle of a forest well-known for its peace. Lastly, in order to support the development and sustainability of the Pondok Management, Pondok Modern Darussalam Gontor has cadre-ization program.